Pengaruh Etika Bisnis Islam Terhadap Kepuasan Konsumen Sakinah Swalayan Di Surabaya - Agus Sarwo Edi; Erwan Aristyanto (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to determine and describe the effect of Islamic business ethics (honest, quality, good relations and transparent prices) on the satisfaction of supermarkets in sakinah consumers in Surabaya. Respondents of the analysis in this study were 100 people sakinah supermarket consumers in the Keputih Village, Sukolilo District, Surabaya City. Samples were taken by using incidental sampling which used samples based on chance meeting with the researcher if it was deemed a suitable person as a data source and purposive sampling with sampling carried out with certain considerations, taking into account the desired respondents to facilitate research. Based on the results of data analysis using the t test, it is known that partially (honest, quality, good relations, transparent prices) have a positive and significant effect on (consumer satisfaction) sakinah supermarkets in Surabaya. Meanwhile, based on the results of data analysis using the F test, it is known that simultaneously (honest, quality, good relations, transparent prices) has a positive and significant effect on consumer satisfaction at supermarkets in Surabaya.Keywords: Honest, Quality, Good Relations, Transparent Prices, Consumer Satisfaction